텍스트 마이닝을 이용한 터널 교통안전 연구동향 분석 - 김진국(Jinguk Kim); 양충헌(Choongheon Yang); 박수빈(Subin Park) (디지털콘텐츠학회논문지, 2022)
최근 수도권, 부산 등을 중심으로 지하도로 건설이 지속적으로 증가하고 있다. 국내에서는 터널과 관련된 많은 연구들이 현재까지 활발하게 이어져 오고 있으나, 최근 국내에 첫 도입되어 운영 중인 지하도로의 경우 관련 연구를 거의 찾아볼 수 없는 실정이다. 따라서, 본 논문에서는 과거 약 20년 동안 국내 저널에 게재된 터널의 교통안전과 관련된 연구동향 분석을 통해 향후 지하도로 운영시 교통안전 확보를 위해 필요한 연구주제를 도출하였다. 비정형 자료 분석에 주로 사용되는 텍스트마이닝(Text mining) 기법 중 LDA(Latent Dirichlet Allocation) 토픽 모델링(Topic modeling)을 사용하여 연구동향을 분석하고 도출된 토픽별 키워드를 기반으로 토픽들을 분석하였다. 본 연구는 텍스트 마이닝을 통해 지하도로의 교통흐름을 안전하게 유도할 수 있는 교통안전 관련 연구의 방향성을 제시하였다는 데 의의가 있다. 향후 지하도로 운영에 있어 교통안전 확보를 위한 연구주제의 방향성을 설정하는데 기초자료로 활용될 수 있을 것으로 판단된다. Recently, construction of underground roads has been continuously increasing in the metropolitan area and Busan. Many studies related to tunnels have been conducted so far, but there are few related studies on underground roads that were recently introduced and operated for the first time. Therefore, this paper in the past about 20 years, local journals published in the next underground roads through the traffic safety-related research and trend analysis of the tunnel traffic safety during operations to secure the necessary research derived. Among the text mining techniques commonly used in unstructured data analysis, research trends were analyzed using LDA-based topic modeling, and topics were analyzed based on the keywords for each topic derived accordingly. This study is meaningful in that it presented the direction of traffic safety-related research that can safely induce traffic flow to underground roads through text mining. This results imply that research trend analysis results would be useful to establishing traffic operation researches and strategies for traffic safety when constructing and opening underground roads in urban areas in the future. KCI Citation Count: 8